2009
DOI: 10.1213/ane.0b013e3181a0b6c6
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Management of Trauma Patients

Abstract: The management of massively transfused trauma patients has improved with a better understanding of trauma-induced coagulopathy, the limitations of crystalloid infusion, and the implementation of massive transfusion protocols (MTPs), which encompass transfusion management and other patient care needs to mitigate the “lethal triad” of acidosis, hypothermia, and coagulopathy. MTPs are currently changing in the United States and worldwide because of recent data showing that earlier and more aggressive transfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 60 publications
(85 reference statements)
0
79
0
8
Order By: Relevance
“…Finally, recent basic science and clinical research has identified a potentially harmful ''storage lesion'' in transfused red blood cell units. 13,50 These biochemical and physical changes include intracellular 2,3-diphosphoglycerate depletion that decreases oxygen offloading from hemoglobin, a stiffer cell membrane that reduces red blood cell flow through capillaries, and decreased bioavailability of nitric oxide necessary for microcirculatory vasodilation. These alterations, together with other biological substances present in preserved red blood cell units, may reduce oxygen delivery and stimulate inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, recent basic science and clinical research has identified a potentially harmful ''storage lesion'' in transfused red blood cell units. 13,50 These biochemical and physical changes include intracellular 2,3-diphosphoglycerate depletion that decreases oxygen offloading from hemoglobin, a stiffer cell membrane that reduces red blood cell flow through capillaries, and decreased bioavailability of nitric oxide necessary for microcirculatory vasodilation. These alterations, together with other biological substances present in preserved red blood cell units, may reduce oxygen delivery and stimulate inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the 10-year timeframe (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001) for data collection because the hospital's trauma registry and blood bank database included cases from this period and available research personnel could feasibly collect data for identified cases. Although massive transfusion is variably defined, our definition is common 3,13 and has been locally adopted. During the period of the study, the hospital had approximately 450 acute care beds with a median of 664 (range, 467-864) admissions per year due to trauma; 488 (range, 344-628) of the admissions had an injury severity score (ISS) C16.…”
Section: Setting and Patientsmentioning
confidence: 99%
“…Recent studies have found that early detection of coagulation, early and active intervention of blood component proportion is extremely significant in patients with severe trauma. MT of almost whole blood markedly reduces mortality (32). Therefore, fixed blood component ratios improve the use of blood components and reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The short period of hypothermia was not enough to cause substantial changes in hemostasis. Planned hemodilution differs from hemodilution secondary to trauma and large blood loss 28 . In planned hemodilution, the blood volume and temperature are maintained, without a large consumption of platelet and coagulation factors.…”
Section: Discussionmentioning
confidence: 99%